Muscular, vascular, and neurological impacts from a giant lipoma in the arm - Ethan L. Snow; Satera Nelson; Andrew C. White (Elsevier, 2023)
Introduction: Lipomas are slow-growing, mesenchymal fatty tumors derived from primordial adipocytes, hereditary disorders, or trauma. They are typically subcutaneous, relatively small (<5 cm), and rarely develop in the upper limb. The objective of the present study was to analyze a giant intermuscular lipoma in the arm and its effects on contiguous muscles, vessels, and nerves. Methods: A giant lipoma in the anterior compartment of a left arm was discovered during routine dissection on an embalmed human cadaveric donor. Gross examination, ultrasonography, and histological analyses were performed on the involved anatomy, and architectural measurements of the impacted muscles were collected to calculate and inform biomechanical impact. Results: The 18.4 cm long, 318.65 g, ovate lipoma displaced the biceps brachii muscle laterally and stretched the coracobrachialis muscle and musculocutaneous nerve around its medial border. In effect, the left biceps brachii muscle's insertion angle was increased from 7.4° to 14.9°, essentially doubling its torque (from 38.26 N·cm to 76.39 N cm). The lipoma also increased the left coracobrachialis muscle's insertion angle (from 15.1° to 34.6°) and torque (from 49.25 N·cm to 114.48 N cm). The walls of the brachial artery contained elastin density inconsistencies and plaque buildup where the lipoma compressed the vessel. Conclusions: While aesthetics and irritation are typical chief complaints of patients with giant lipomas, this study shows how nerve impingement, biomechanical impact, and vascular compression may also present as sequelae. This study may inform physicians when working to diagnose and treat giant lipomas, hereditary multiple lipomatosis, adiposis dolorosa, Madelung's disease, and other related conditions.